PERFORMANCE CRITERIA SLITTING-PROCESS - N. V. Starkov; Yu. L. Bobarykin (Литьë и металлургия)
Criteria of efficiency the slitting process. For example double-line rolling of rebar No. 20 identified such criteria separation efficiency in non-dividing device as the size of the crossbar.